Expanded Horizon of Perforator Flap: A Game Changer in Reconstructive Plastic Surgery (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Abstract not availableJ Bangladesh Coll Phys Surg 2026; 44: 79-80